2019
DOI: 10.1097/md.0000000000014604
|View full text |Cite|
|
Sign up to set email alerts
|

Clinical efficacy and safety of Tripterygium wilfordii Hook in the treatment of diabetic kidney disease stage IV

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 17 publications
3
17
0
Order By: Relevance
“…In our present meta-analysis, 26 clinical studies including 1824 subjects (939 in experiment group and 885 in control group) were included. we found the TGs groups howed signi cant effects in reducing 24-UTP (P < 0.05), elevating Alb (P < 0.05), reducing Scr (P < 0.05), elevating Ccr (P < 0.05), and increasing the total e ciency, when compared to the control group, which is the same as others meta-analysis [11,45,46] . However, TGs treatment had no obvious advantage in improving BUN (P > 0.05) and increasing ALT (P > 0.05), The adverse effects of bone marrow suppression is obvious in TGs group, there was signi cant effect in reducing WBC (P < 0.05), when compared to the control group.…”
Section: Discussionsupporting
confidence: 85%
“…In our present meta-analysis, 26 clinical studies including 1824 subjects (939 in experiment group and 885 in control group) were included. we found the TGs groups howed signi cant effects in reducing 24-UTP (P < 0.05), elevating Alb (P < 0.05), reducing Scr (P < 0.05), elevating Ccr (P < 0.05), and increasing the total e ciency, when compared to the control group, which is the same as others meta-analysis [11,45,46] . However, TGs treatment had no obvious advantage in improving BUN (P > 0.05) and increasing ALT (P > 0.05), The adverse effects of bone marrow suppression is obvious in TGs group, there was signi cant effect in reducing WBC (P < 0.05), when compared to the control group.…”
Section: Discussionsupporting
confidence: 85%
“…A meta-analysis of RCTs carried out in patients with stage 4 diabetic CKD showed that TwHF combined with an ARB was more effective than an ARB alone when considering 24 h proteinuria and serum albumin, but with an increase in AE frequency of 8% [32]. A recent review indicated that TwHF-based therapies for CKD in mainland China were more effective in improving proteinuria, blood creatinine levels, and blood urea nitrogen levels than conventional Western medicine alone or other immunosuppressive regimens [33].…”
Section: Discussionmentioning
confidence: 99%
“…Tripterygium glycoside, an extract from a natural herb Tripterygium Hook. f. with strong immunosuppressive and anti-inflammatory effects, has been reported to decrease proteinuria and improve renal dysfunction in DKD through numerous randomized controlled clinical trials [45, 63]. In high-glucose serum from db/db mouse induced podocytes, tripterygium glycoside intervention significantly decreased apoptotic activity, along with elevated LC3-II/LC3-I ratios and reduced expression of p62 [18].…”
Section: Mechanisms Of Chinese Herbal Medicine Treating Dkd Via Acmentioning
confidence: 99%